Growth and yield response of broccoli (Brassica oleracea var. italica) to varying drip irrigation and fertigation levels - KAPOOR, RENU; SANDAL, SANJEEV KUMAR (The Indian Journal of Agricultural Sciences, 2019)
The study was conducted during 2013–14 and 2014–15 at experimental farm of Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Palampur with the objective to evaluate the effect of drip irrigation and NPK fertigation levels on crop growth, nutrient uptake, nutrient use efficiency and productivity of broccoli (Brassica oleracea var. italica) The treatment combinations comprised two irrigation levels (0.4 and 0.8 CPE), four fertigation levels (50, 100, 150 and 200% RDF), one farmer’s practice (FYM @ 1 kg/m2 + 10 g/m2 IFFCO (basal) + 2 g/L of 19:19:19 at 15 days intervals and drip irrigation applied @ 2 L/m2 daily), and one recommended practice (100% RDF by conventional method + drip irrigation at 100% CPE). The results revealed that plants grown under fertigation had more number of leaves and plant height as compared to those grown under conventional method. Study on drip fertigation revealed that root length, volume and mass were significantly higher with F200 over F100 and F50 leading to higher marketable yield. However, fertigation treatment F50 resulted in high nutrient use efficiency and saving of 50% and 20–60% fertilizers and water, respectively, as compared to conventional fertilization with drip irrigation at I1.0 to maintain the same yield levels in broccoli.